2020
DOI: 10.3390/cells9040811
|View full text |Cite
|
Sign up to set email alerts
|

Directed Differentiation of Mobilized Hematopoietic Stem and Progenitor Cells into Functional NK Cells with Enhanced Antitumor Activity

Abstract: Obtaining sufficient numbers of functional natural killer (NK) cells is crucial for the success of NK-cell-based adoptive immunotherapies. While expansion from peripheral blood (PB) is the current method of choice, ex vivo generation of NK cells from hematopoietic stem and progenitor cells (HSCs) may constitute an attractive alternative. Thereby, HSCs mobilized into peripheral blood (PB-CD34+) represent a valuable starting material, but the rather poor and donor-dependent differentiation of isolated PB-CD34+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Peripheral blood contains NK cells and is a reliable source of CD34 progenitor cells from individuals undergoing GCS-F mobilization ( 34 ). Isolating large numbers of PB NK cells and hematopoietic stem cells is difficult as the percentage derived from leukapheresis can be low and highly variable ( 22 , 35 , 36 ).…”
Section: Sources Of Natural Killer Cells For Immunotherapymentioning
confidence: 99%
“…Peripheral blood contains NK cells and is a reliable source of CD34 progenitor cells from individuals undergoing GCS-F mobilization ( 34 ). Isolating large numbers of PB NK cells and hematopoietic stem cells is difficult as the percentage derived from leukapheresis can be low and highly variable ( 22 , 35 , 36 ).…”
Section: Sources Of Natural Killer Cells For Immunotherapymentioning
confidence: 99%
“…Membrane IL-21 alone [ 39 ] and IL-21 in combination with IL-15 [ 40 , 41 , 42 ] promotes the expansion of NK cells ex vivo with preclinical studies establishing efficacy against solid tumors. Several clinical trials also show the value of using IL-21 alone against metastatic melanoma, but drug combinations have yielded mixed outcomes [ 43 , 44 ].…”
Section: Modifying Nk Cells To Be Better Effector Cellsmentioning
confidence: 99%
“…A recent study by Oberoi et al [ 42 ] showed that healthy donor PB can serve as a valuable starting material for creating hematopoietic stem and progenitor cells (HSCs), despite earlier studies indicating poor and donor-dependent differentiation [ 172 , 173 , 174 , 175 , 176 ]. This was due to a refined approach to differentiation and expansion protocols that utilized optimized cytokine cocktails and expansion enhancement with K562 feeder cells, co-expressing 4-1BB ligand and mbIL-15 and IL-21 [ 42 ] (see Section 3.1 ). As healthy PB is readily available and easier to access compared to umbilical cord blood (UCB) and human embryonic stem cells (hESCs), this protocol may serve as an economically viable option for NK cell generation.…”
Section: Off-the-shelf Nk Cells For Cancer Immunotherapymentioning
confidence: 99%
“…However, two major aspects of human NK cells, the marked resistance to standard genetic modifications with lentiviral vectors and the limited ex vivo expansion capacities, have hampered their use for both allogeneic and also autologous CAR-redirected immunotherapies. Hence, researchers have resorted to stable NK cell lines, such as NK-92 (36)(37)(38)(39)(40)(41)(42), or to using NK cells differentiated from CD34+ hematopoietic stem and progenitor cells (HSPCs) or pluripotent stem cells (PSCs) (43)(44)(45)(46) with subsequent expansion using feeder cells (47)(48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%